Deoxynucleoside therapy for respiratory involvement in adult patients with thymidine kinase 2-deficient myopathy - Cristina Domínguez-González; Ana Hernandez-Voth; Javier Sayas Catalan; Marta Corral Blanco; Alba Castaño Mendez; Miguel Angel Martin; Carlos De Fuenmayor Fernandez de la Hoz; Victoria Villena Garrido (BMJ Open Respiratory Research)
Background Recessive mutations in the thymidinekinase 2 (TK2) gene cause a rare mitochondrial myopathy, frequently with severe respiratory involvement. Deoxynucleoside therapy is currently under investigation.Research question What is the impact of nucleosides in respiratory function in patients with TK2-deficient myopathy?Study design and methods Retrospective observational study of patients treated with deoxycytidine and deoxythymidine. Evaluations were performed every 3 to 4 months after treatment during approximately 30 months. Forced vital capacity (FVC), maximuminspiratory and expiratory pressures (MIP/MEP), sniff nasal inspiratory pressure (SNIP), cough peak flow (CPF), arterial blood gas and nocturnal pulse oximeter (SpO2) were collected.Results We studied six patients, five of which were women, with a median age at onset of symptoms was 35.8 (range 5 to 60) years old. Patients presented a restrictive ventilatory pattern (median FVC of 50 (26 to 71)%) and severe neuromuscular respiratory weakness (MIP 38 (12 to 47)% and SNIP 14 (8 to 19) cmH2O). Four patients required ventilatory support before starting the treatment. FVC improved by 6%, proportion of sleep time with SpO2 <90% diminished from 14% to 0%, CPF increased by 23%, MEP increased by 73%, production and management of bronchial secretions improved and respiratory infections diminished.Interpretation Early detection of respiratory involvement requires an active search, even in asymptomatic patients. The nucleosides therapy may improve respiratory function, and stabilise the loss of respiratory capacity.